Staying with the trouble of institutions. Issue 2 (5th February 2019) - Philo, Chris; Parr, Hester
Abstract : This paper provides a commentary on the theme section entitled "Troubling Institutions at the Nexus of Care and Control." Using the recent book Matters of Care (2017) by Maria Puig de la Bellacasa as a reference point, the authors of the commentary introduce the project of exploring how care and control admix across a range of institutional geographies, reflecting complex assemblages of places, peoples, practices and problems. Taking seriously the prompt by the section editors to think about the "troubling" of institutions, the authors draw provisional distinctions between those that are "troubled" and those that are "troublesome, " mapping across to the range of more‐or‐less institutional – more‐or‐less carceral – spaces considered in the papers comprising the theme section. The commentary concludes with attention, inspired by Donna Haraway's notion of "staying with the trouble, " to the task of staying both with the troubles bundled up in institutional landscapes and, indeed, with the very idea and practice of institutions themselves. Abstract : This paper provides a commentary on the special section entitled 'Troubling Institutions at the Nexus of Care and Control.' Using the recent book Matters of Care (2017) by Maria Puig de la Bellacasa as a reference point, the authors of the commentary introduce the project of exploring how care and control admix across a range of institutional geographies, reflecting complex assemblages of places, peoples, practices and problems.